Idempotent elements of the semigroup B_X (D) defined by semilattice of the class ∑_2(X,5) - Bakuridze, Aleksandre; Givradze, Omar; Didmanidze, Ibraim; Didmanidze, Tengiz (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article discusses complete semigroups of binary relations defined by semilattices of the class . It is described idempotent elements of complete semigroups of binary relations defined by semilattices of the class . In the case of finite semigroups, the formula for calculating idempotent elements is obtained. It is shown that the order of any subgroup of a semigroup does not exceed 2